Common Mistakes in Chinese Stroke Writing Among NonChinese Learners - Chuah, Kee Man; Ch’ng, Looi-Chin; Ting, Hie Ling (UiTM Cawangan Johor, Malaysia, 2018)
The learning of stroke writing is a complicated process yet it is viewed as a fundamental element in Chinese language learning. This has brought great challenges to many learners especially non-native learners. This study aims to identify the types of stroke writing mistakes and the frequency of making the mistakes among the non-native learners. A dictation of 68 words was given to all 50 Foundation Mandarin level 2 Diploma students from Faculty of Business Administration. The words were extracted from their stroke writing exercises in the course’s text book. Data suggested that Stroke Misalignment, Stroke’s Shape and Non-existing Strokes are prominent mistakes done by the learners. The findings of the study recommend that stroke order might be one of the most impactful component to minimize stroke mistakes among the non-native learners. However, further studies need to be done to investigate the teaching methods that can deliver such component effectively.